2019
DOI: 10.4236/jss.2019.73022
|View full text |Cite
|
Sign up to set email alerts
|

The Game of Monetary Policy, Inflation and Economic Growth

Abstract: Ghana has been confronted with series of economic problems to the extent of calling on the IMF for a bailout after every eight years. This situation has persisted in spite of various monetary authority stabilization policies. This paper therefore focuses on investigating the games of monetary policy, inflation and economic growth of the Ghanaian economy for the period of 1982-2017. Using Autoregressive Distributed Lag (ARDL) to cointegration model, it was revealed from the study that in the long run interest r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Economist Robert Lucas also developed the idea of the final determination of the relationship of the factors under consideration. He has already changed some methodological approaches, and began to study inflation expectations in the economy, as a result of which he came to the conclusion of a sufficiently high explanatory power of the Phillips model in the short term, but the need for significant refinement and customization for the purpose of the study when trying to apply it over a long period of time [88][89][90][91].…”
Section: Discussionmentioning
confidence: 99%
“…Economist Robert Lucas also developed the idea of the final determination of the relationship of the factors under consideration. He has already changed some methodological approaches, and began to study inflation expectations in the economy, as a result of which he came to the conclusion of a sufficiently high explanatory power of the Phillips model in the short term, but the need for significant refinement and customization for the purpose of the study when trying to apply it over a long period of time [88][89][90][91].…”
Section: Discussionmentioning
confidence: 99%
“…Wauk and Ajorlolo [15] investigated the games of monetary policy, inflation and economic growth of the Ghanaian economy for the period of 1982 to 2017 using ARDL to cointegration model. The study revealed a significant negative relationship between interest rate and economic growth, and insignificant relationship between economic growth and exchange rate.…”
Section: Brief Literature On the Dynamic Interrelationships Among Inf...mentioning
confidence: 99%
“…A case study in China by Wank and Adjorlolo (2019) revealed that long run interest rate significantly influences economic growth both in the negative and positive direction. This implies that higher interest rate has the tendency to restrict economic growth and inflationary pressure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They recommended that the Bank of Ghana should be autonomous and the state should not interfere in its functions. Therefore, the macro economic variables that affects economic growth is interest rate and the exchange rate (Wank and Adjorlolo, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%